JOB SATISFACTIONAND PERFORMANCEOF EMPLOYEESOFOVERSEAS COOPERATION MANAGEMENT BOARDIN WEST JAVA PROVINCIAL GOVERNMENT - Rinta Suhardi, Agatha; Ayudia Adiyanti, Siska; Oktafien, Shinta; Rohendra, Titto (International Journal of Psychosocial Rehabilitation, 2020)
Based on the analysis that job satisfaction affects the performance of employees in the Agency Management Foreign Cooperation of the West Java Regional Government. Building and developing employee performance can be done through increasing the job satisfaction of its employees. Based on the research design considerations, this research includes explanatory research because this study intends to explain the causal relationship between variables through hypothesis testing. The unit of analysis of this study is individuals, namely employees Cooperation Agency of the West Java Regional Government as members of the organization. From the results of the analysis it can be shown that there is an influence of job satisfaction on the performance of employees as members of the organization. While the direction of the positive regression coefficient (0.948) shows that with increasing job satisfaction members of the organization will also improve the performance of employees as members of the organization.